Editorial: Gains and Challenges in the Global Movement for Sex Workers’ Rights - Lepp, Annalee; Gerasimov, Borislav (Anti-Trafficking Review, 2019)
Over the past two decades, there has been a growing body of excellent academic and community-based literature on sex workers’ lives, work, and organising efforts, and on the harmful effects of anti-trafficking discourses, laws, and policies on diverse sex worker communities. Importantly, a significant portion of this work has been produced by sex workers and sex worker organisations.[1] When we decided to devote this Special Issue of Anti-Trafficking Review to the theme of sex work, we acknowledged this reality. However, we also thought that, given that the discourses, laws, and policies that directly impact sex workers globally are continually changing, the production of new evidence-based research and critical perspectives is constantly needed.